Antimutagenic effect of grape seed extracted oil on diazinon induced genotoxicity in albino mice - Al-Attar, Mustafa S. (Iraqi Journal of Cancer and Medical Genetics, 2017)
Background: Human health hazard due to exposure to chemical pollutants is a global and chronic problem. The pesticides constitute the primary toxic chemicals in the environment. The present study explored the effects of grape seed oil supplementation on diazinon (DZN) induced chromosomal aberrations and sperm abnormalities in male mice. Materials and methods: The tests were carried out on 35 adult male albino mice (16-20 weeks, weighed 30-35 g). Animals were categorized into seven groups each with five mice; the first group was treated with phos¬phate buffer saline (PBS) as negative control group. The second and third groups were treated daily and orally with two different doses of the DZN (60 and 90 mg/kg body weight) respectively dissolved in corn oil. Animals of fourth, fifth and sixth groups were orally administered grape seed oil at a dose of 2 g/kg body weight, after 6 hours the fourth and fifth groups subjected to DZN at the same dose given to second and third groups. Animals of the seventh group were supplied with corn oil. The treatments were continued for five weeks. Results: The results showed that DZN increased the frequency of both chromatid and chromosome aberrations in bone marrow cells and sperm abnormalities. Treatment with grape seed oil extract showed a significant decrease (P